Time to prepare the way in the wilderness : papers on the Qumran scrolls - Dimant, Devorah.; Schiffman, Lawrence H. (Studies on the Texts of the Desert of Judah, 1995)
This collection of articles on the Dead Sea Scrolls by fellows at the Institute for Advanced Studies of The Hebrew University (1989-1990) represents the ongoing work of editing and interpreting one of the greatest archaeological discoveries of the century. This volume includes articles on the contents and significance of the scrolls, the biblical scrolls, the legal rulings of the sectarians and their prayer texts.